Construção da Agroecologia como projeto socialmente transformador: ação coletiva de mulheres guardiãs de sementes crioulas - Vanconcellos, Andreia (2020)
In the territory of Borborema, state of Paraíba, several social agents linked to unions and movements of landless workers, with the support of social mediators from non-governmental organizations, mobilized women, men and young peasants in rural development processes, based on Agroecology, as a strategy for environmental preservation and socio-productive insertion. Important social actions were oriented towards the production and custody of Creole seeds, locally called “Seeds of Passion”. The doctoral thesis aims to understand the social processes and relationships woven by rural women and young rural women in the construction of practices and social representations of custody of Creole seeds. The research was conducted as a case study, carried out in the municipality of Remígio, state of Paraíba. The criterion for choosing Remígio was the relevance of the participation of women and young women in planting and guarding Creole seeds. The research followed a qualitative approach, using semi-structured interview techniques and participatory observations, carried out in women's homes and in participation in events, workshops and anniversaries. In a complementary way, a survey of documents related to the processes of participation of women and young peasants around creole seeds and struggles for rights was carried out. The articulation of multiple social agents, representing the peasants and rural development, triggered important processes of participation of peasant women in the struggles in defense of the environment, of agroecology, of Creole seeds, of the female insertion in the production and commercialization of agroecological products. In the combination of ancestral knowledge and techniques with agroecological knowledge, made available by social mediators, the family farmers of guard produce various crops and creations, which generate food security for their families and also marketable surpluses at the Agroecological Fairs, which guarantee their own income and financial autonomy. Peasant women associate their Creole seeds with a universe of social representations, which are expressed in the work of planting, harvesting, eating and keeping, in ancestral ties and teachings, in ties with land and water, in community celebrations, in religious beliefs, food and health care for people and animals. Young peasant women also began to organize themselves around the expansion of spaces for expression and social struggles, agroecological production, the guarding of creole seeds, of productive and market insertions, as ways to ensure their social reproduction and develop their projects of social emancipation. Women and young rural women become fundamental social agents in rural development processes, experienced in Remígio, due to their significant participation in the preservation of natural resources, in the strengthening of food production, in the construction of agroecological markets and in the advances in female emancipation.